2012
DOI: 10.1186/1471-2334-12-352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of smear positive pulmonary tuberculosis among prisoners in North Gondar Zone Prison, northwest Ethiopia

Abstract: BackgroundPeople concentrated in congregated systems, such as prisons, are important but often neglected reservoirs for TB transmission, and threaten those in the outside community. Therefore, this study was conducted to determine the prevalence of tuberculosis in a prison system of North Gondar Zone.MethodsAn active case-finding survey in North Gondar Prison was carried out from March to May 2011. All prison inmates who had history of cough for at least a week were included in the study. Three morning sputum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
71
18
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 16 publications
16
71
18
4
Order By: Relevance
“…The prevalence of this study was higher than the studies conducted in Bangladesh 13.8 % [9], Cameron 1.2% [13], Brazil 2.5% [19], Iran 0.91% [20], Malawi 0.7% [22] and North Gonder, Ethiopia 8.9% [23]. On the other hand, the prevalence of this study was lower than the studies conducted in Nigeria 54.2 % [4] and Pakistan 26.3 % [21].…”
Section: Discussioncontrasting
confidence: 47%
“…The prevalence of this study was higher than the studies conducted in Bangladesh 13.8 % [9], Cameron 1.2% [13], Brazil 2.5% [19], Iran 0.91% [20], Malawi 0.7% [22] and North Gonder, Ethiopia 8.9% [23]. On the other hand, the prevalence of this study was lower than the studies conducted in Nigeria 54.2 % [4] and Pakistan 26.3 % [21].…”
Section: Discussioncontrasting
confidence: 47%
“…To our knowledge, there are ten published datasets that describe TB in prisons in SSA. These data reported high prevalence and incidence rates of TB compared to the general population [2,5,[14][15][16][17][18][19][20]28]. For instance, in an active case-fi nding survey in Madagascar [28], the prevalence of TB in Antananarivo prison was 16 times higher and Zambian prisons [2] had about 10-fold higher incidence than in the general population.…”
Section: Evidence Of Prevalence Of Tb In Prisonsmentioning
confidence: 95%
“…In this review, we observed that, globally, the level of TB in prisons has been reported much higher than that of TB in the general population [1,2,5,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The WHO estimated a prevalence of TB in prisons about 10-to 100-fold higher than the prevalence in the general population [30].…”
Section: Evidence Of Prevalence Of Tb In Prisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Data from this study show that a signifi cantly higher number of Malays were incarcerated in a correctional facility at the moment of notifi cation. However, using available data, it cannot be ascertained whether more Malay inmates had TB, or whether the proportion of Malays was the same among inmates with TB and among all inmates in Singapore.…”
Section: Public Health Action Tuberculosis and Ethnicity In Singaporementioning
confidence: 98%